Tacrolimus: Physicochemical stability challenges, analytical methods, and new formulations - Sara Sajjadi; Ali Shayanfar; Farhad Kiafar; Mohammadreza Siahi-Shadbad (Elsevier, 2024)
Tacrolimus, a potent immunosuppressant, is widely used in several formulations to treat organ rejection in transplant patients. However, its physicochemical stability poses significant challenges, including thermal instability, photostability issues, low solubility, and drug-excipient incompatibility. This review article focuses on the details of these challenges and discusses the analytical methods employed to study tacrolimus stability, such as thermal, spectroscopic, and chromatographic methods in different formulations. New formulations to enhance tacrolimus stability are explored, including lipid-based nanocarriers, polymers, and thin film freezing. Researchers and formulators can optimize tacrolimus formulations to improve efficacy and patient outcomes by understanding and addressing these stability challenges.